PERCEIVED BENEFITS OF E-LEARNING TECHNOLOGIES BY BUSINESS EDUCATION STUDENTS: IS AVAILABILITY A CONCERN IN UNIVERSITIES (NAU Journal of Technology and Vocational Education, 2024)
The study explored the benefits of e-learning technologies in business education programmes inuniversities by considering the concerns of the availability of the technologies. Two researchquestions and two hypotheses were raised and formulated respectively to guide the study. Thestudy adopted a descriptive survey research design. The population of the study comprised 521Business Education students at the University of Benin and Benson Idahosa University, out ofwhich 100 students were used as a sample, using the disproportionate stratified random samplingtechnique. A structured questionnaire containing 17 items was the instrument used for datacollection. Having validated the instrument, its reliability was determined using Cronbach’salpha method, which yielded a coefficient 0.84. Data collected were analyzed using mean andstandard deviation for the research questions, while t-test and Analysis of Variance (ANOVA)were used to test the hypotheses. The findings of the study revealed that students had severalpositive perceptions about e-learning technologies for enhancing business education programmeto bridge the gap that exists between theories and practice in learning. However, availability ofthe e-learning resources is a concern because students perceived that the resources were notavailable in their institutions as expected. Based on the findings it was recommended thatrelevant shareholders in education should provide adequate e-learning technologies for theteaching and learning process of business education courses.
Keywords: Availability, benefits, business education programme, e-learning technologies